In vitro Antimicrobial Activity of Robenidine, Ethylenediaminetetraacetic Acid and Polymyxin B Nonapeptide Against Important Human and Veterinary Pathogens - Khazandi, Manouchehr; Pi, Hongfei; Chan, Wei Yee; Ogunniyi, Abiodun David; Sim, Jowenna Xiao Feng; Venter, Henrietta; Garg, Sanjay; Page, Stephen W.; Hill, Peter B.; McCluskey, Adam; Trott, Darren J. (Frontiers in Microbiology, 2019)
The emergence and global spread of antimicrobial resistance among bacterial pathogens demands alternative strategies to treat life-threatening infections. Combination drugs and repurposing of old compounds with known safety profiles that are not currently used in human medicine can address the problem of multidrug-resistant infections and promote antimicrobial stewardship in veterinary medicine. In this study, the antimicrobial activity of robenidine alone or in combination with ethylenediaminetetraacetic acid (EDTA) or polymyxin B nonapeptide (PMBN) against Gram-negative bacterial pathogens including those associated with canine otitis externa was evaluated in vitro using microdilution susceptibility testing and the checkerboard method. Fractional inhibitory concentration indices (FICIs) and dose reduction indices (DRI) of the combinations against tested isolates were determined. Robenidine alone was bactericidal against Acinetobacter baumannii (MIC mode = 8 µg/ml) and A. calcoaceticus (MIC mode = 2 µg/ml). Against Acinetobacter spp., an additivity/indifference of the combination of robenidine/EDTA (0.53>FICIS>1.06) and a synergistic effect of the combination of robenidine/PMBN (0.5<FICI) against Acinetobacter spp. were obtained. DRIs of robenidine were significantly increased in the presence of both EDTA and PMBN from 2- to 2048-fold. Robenidine exhibited potential antimicrobial activity against Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa, in the presence of sub-inhibitory concentrations of either EDTA or PMBN. Robenidine, also demonstrated potent antibacterial activity against multidrug-resistant Gram-positive pathogens and all Gram-negative pathogens isolated from cases of canine otitis externa in the presence of EDTA. Robenidine did not demonstrate antibiofilm activity against Gram-positive and Gram-negative bacteria. EDTA facilitated biofilm biomass degradation for both Gram-positives and Gram-negatives. However, the addition of robenidine to EDTA was not associated with any change in the effect on biofilm biomass degradation. The combination of robenidine with EDTA or PMBN has potential for further exploration and pharmaceutical development, for example incorporation into topical and otic formulations for animal or possible human use.